Concentration and Characteristic of Floating Plastic Debris in Jakarta Bay: a Preliminary Study - Dwiyitno Dwiyitno; Fairdiana Andayani; Umi Anissah; Hedi Indra Januar; Singgih Wibowo (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2020)
Marine debris, especially plastic debris, is becoming global awareness, including in Indonesia, due to the possible harmful effects on the environment and humans. The present study is the first assessment of the floating plastic debris in Jakarta Bay based on an at-sea survey. The study aimed to overview the accumulation of plastic debris in different zones (west, middle, and east) of the bay as the impact of wet and dry seasons. The results showed that plastic debris was found in most sampling stations with a maximum concentration of 10,300 and 7,400 items/km2 in the wet and dry seasons, respectively. Based on the plastic types, polyethylene (PE), polypropylene (PP), and polystyrene (PS) were the main accumulated plastic debris in Jakarta Bay with a predominant macro size between 2.5 and 20 cm. According to the plastic applications, packaging and consumer products were the majority of plastic debris at concentrations of 257-1,280 items/km2 and 936-983 items/km2 in the dry and wet season respectively. The spatial distribution of plastic litter in the observed surface water was correlated to temporal monsoon seasons rather than to the distribution of pollution source from rivers around the Jakarta Metropolitan Area. Moreover, the higher plastic concentration was found in the rainy west monsoon compared to that of the dry east monsoon.